Frequency of Chromosome Disorders In Patients with Sperm Number Anomaly - Mehmet Niyaz; Egzon Abdullahı; Zerrin Yılmaz Çelik (Gazi Medical Journal)
Objective: Chromosome abnormalities play an important role in male infertility. The rate of chromosome disorders in infertile men is higher as 5.8% when compared to the normal population (0.5%). Methods: This study aimed to determine the frequency of cytogenetic abnormalities in infertile men with abnormal sperm counts and to show that rare chromosomal rearrangements can be detected by karyotyping. Results: In our clinical practice, we detected nearly all chromosome numerical and structural anomalies involved in infertility. It includes inversions, translocations, deletions, insertions, complex rearrangements, isochromosomes, Klinefelter syndrome, mosaicism, and 47, XYY. Conclusion: Our results emphasize the importance of conventional cytogenetic analysis for infertile males. The detection of rare or known chromosome abnormalities will prevent unnecessary investigations and enable us the application of precision in medicine.